Prescribed-Time Time-Varying Multi-Group Formation Tracking Control of NMSVs via Estimator-Based Hierarchical Control Algorithm - Chen, Lin-Jing; Han, Tao; Xiao, Bo; Yan, Huaicheng (IEEE transactions on intelligent vehicles, 2023)
This article considers the time-varying multi-group formation tracking control (MGFTC) problem in a prescribed time for the networked marine surface vehicles (NMSVs) facing the case of the external disturbances. To handle such a complicated issue, the prescribed-time estimator-based hierarchical control (PTEBHC) scheme is constructed. More notably, the convergence time can be randomly predetermined according to practical demand. In the light of the Lyapunov stability theory, the sufficient conditions for ensuring the prescribed-time stability of the closed-loop system are obtained. Eventually, the corresponding simulations are presented to demonstrate the feasibility and effectiveness of the constructed algorithms.